Fibulin-3 Deficiency Protects Against Myocardial Injury Following Ischaemia/ Reperfusion in in vitro Cardiac Spheroids - Sharma, Poonam; Beck, Dominik; Murtha, Lucy A.; Figtree, Gemma; Boyle, Andrew; Gentile, Carmine (Frontiers in Cardiovascular Medicine, 2022)
Myocardial infarction (MI, or heart attack) is a leading cause of death worldwide. Myocardial ischaemia reperfusion (I/R) injury typical of MI events is also associated with the development of cardiac fibrosis and heart failure in patients. Fibulin-3 is an extracellular matrix component that plays a role in regulating MI response in the heart. In this study, we generated and compared in vitro cardiac spheroids (CSs) from wild type (WT) and fibulin-3 knockout (Fib-3 KO) mice. These were then exposed to pathophysiological changes in oxygen (O2) concentrations to mimic an MI event. We finally measured changes in contractile function, cell death, and mRNA expression levels of cardiovascular disease genes between WT and Fib-3 KO CSs. Our results demonstrated that there are significant differences in growth kinetics and endothelial network formation between WT and Fib-3 KO CSs, however, they respond similarly to changes in O2 concentrations. Fib-3 deficiency resulted in an increase in viability of cells and improvement in contraction frequency and fractional shortening compared to WT I/R CSs. Gene expression analyses demonstrated that Fib-3 deficiency inhibits I/R injury and cardiac fibrosis and promotes angiogenesis in CSs. Altogether, our findings suggest that Fib-3 deficiency makes CSs resistant to I/R injury and associated cardiac fibrosis and helps to improve the vascular network in CSs.